Pengaruh Pendidikan Terhadap Produktivitas Tenaga Kerja di Sektor Industri Manufaktur - Amahda Nur Aulia; Khoirul Sahita Rahma; Muhammad Ashroful Ardiansyah; Muhammad Yusuf Karim; Nina Farliana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education plays a strategic role in improving labor productivity, particularly in the manufacturing sector which demands high skills and work efficiency. This research aims to analyze the influence of education on labor productivity through a comprehensive literature review approach. Various national and international literature were systematically analyzed to understand how education level contributes to skill improvement, innovation, and labor efficiency. The findings show that workers with higher education levels tend to have better technological understanding, can adapt to industrial changes, and contribute more significantly to production efficiency. Studies in Indonesia indicate a positive correlation between education level and labor productivity in the manufacturing sector, with productivity increases of 5-15% for each higher education level. Additionally, investment in education has proven to positively impact company competitiveness and overall economic growth. This research recommends the need for education policies aligned with industry needs, strengthening link and match programs, and improving vocational curriculum quality to create competent and adaptive workforce in the industrial revolution 4.0 era.